PREVENTATION AND LONG-TERM CONTROL OF BRONCHIAL ASTHMA IN SCHOOL-AGE CHILDREN IN OUTPATIENT PRACTICE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Bronchial asthma remains one of the most common chronic diseases among school-age children. The condition affects physical development, academic performance, and overall quality of life. Effective prevention and systematic control in outpatient care help minimize exacerbations, reduce the need for hospitalizations, and ensure that children can live a full, active life. This article discusses modern methods of prevention and control of bronchial asthma, with an emphasis on patient education, identification and elimination of triggers, and the use of individualized treatment strategies.